Islam dan Kosmopolitanisme Islam pada Dinasti Abbasiyah - Nurabidin, Usman Nurabidin; Ramadhani, Luthfiah Nafi’; Ghina , Arlyya Rectifia Agnar; Abbas, Ngatmin (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2024)
This research addresses the crucial theme of the role of Islam and the concept of cosmopolitanism in maintaining unity and stability of power during the Abbasid Dynasty. With a clear objective, this study aims to define cosmopolitanism within the context of that period, analyze its impact on cultural diversity and social relations, and explore the synergy between Islamic teachings and cosmopolitanism in facing various social challenges. The methodology employed is library research, where the researcher conducts an in-depth analysis of literature from primary and secondary sources related to the history, culture, and politics of the Abbasid Dynasty. This approach enables the researcher to gather comprehensive data relevant for understanding the social dynamics of that time.The results indicate that cosmopolitanism in the Abbasid Dynasty is characterized by an openness to cultural diversity, enriching social interactions within society. This concept successfully created an atmosphere of tolerance that supports cohesion among various ethnic and religious groups. The synergy between Islamic teachings, which emphasize justice, and cosmopolitan values has proven effective in alleviating social tensions and strengthening the legitimacy of Abbasid power.The study also analyzes the role of Islam and cosmopolitanism in the stability and unity of the Abbasid Dynasty. Data is categorized based on relevance to compare different perspectives and identify key themes. A sociological approach is used to examine the social, cultural, and economic influences on the development of Abbasid governance. The findings are expected to enrich historical studies as well as understanding of multiculturalism and social integration.Finally, this research concludes that the collaboration between religion and cosmopolitanism significantly contributes to the creation of a stable and united society. These findings are relevant not only in the historical context of the Abbasid Dynasty but also offer a useful model for modern societies facing contemporary challenges related to diversity. Thus, this research provides valuable insights into how values of tolerance and openness can serve as a foundation for unity in pluralistic societies.